2018
DOI: 10.18632/oncotarget.25952
|View full text |Cite|
|
Sign up to set email alerts
|

Lipolysis-stimulated lipoprotein receptor overexpression is a novel predictor of poor clinical prognosis and a potential therapeutic target in gastric cancer

Abstract: The prognosis of patients with advanced gastric cancer (GC) remains poor despite the recent advances in molecular targeted therapies, and the search for biomarkers that can predict prognosis and additional new agents with acceptable toxicity profiles are needed. Lipolysis-stimulated lipoprotein receptor (LSR) is a lipoprotein receptor that binds to triglyceride-rich lipoproteins and related to some malignancies. Herein, we examined the association between LSR expression and the prognosis of patients with GC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…LSR, a type I single-pass transmembrane protein, is primarily expressed in the liver, intestine, and other tissues [14]. Upregulated LSR was demonstrated in various cancers, including colon, bladder, breast, endometrial, and ovarian cancers [15]. Numerous studies imply that LSR probably participates in the development of multiple cancers [16].…”
Section: Discussionmentioning
confidence: 99%
“…LSR, a type I single-pass transmembrane protein, is primarily expressed in the liver, intestine, and other tissues [14]. Upregulated LSR was demonstrated in various cancers, including colon, bladder, breast, endometrial, and ovarian cancers [15]. Numerous studies imply that LSR probably participates in the development of multiple cancers [16].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the expression of angulin-1/LSR in breast cancer is higher in invasive ductal carcinomas than in invasive lobular carcinomas [ 42 ]. Furthermore, high expression of angulin-1/LSR is a poor prognostic factor in epithelial ovarian cancer and gastric cancer [ 43 , 44 ].…”
Section: Tight Junction Proteins In Endometriosis and Endometrial Cancermentioning
confidence: 99%
“…In gastric cancer, LISCH7 overexpression is proposed to be an independent prognostic factor of poor clinical outcome. 6 Likewise, in human colorectal cancer, elevated LISCH7 expression is tightly associated with disease progression. 29 By contrast, LISCH7 loss promotes cell invasiveness in human endometrial cancer.…”
Section: Tgf-β1 Accounts For Cell Growth Induction Augmentation Of Cellular Invasiveness and Reduction Of Doc Sensitivity In Lisch7-overementioning
confidence: 99%
“…Liver-specific bHLH-Zip transcription factor (LISCH7, also known as LSR) has been identified as a novel molecular constituent of tricellular contacts localized at most epithelial tissues. 4 Emerging evidence points to that LISCH7 may play an important role in the regulation of tight junction formation, 4 cell invasion and migration, 5 cell proliferation, 6 and drug response 7 in different types of malignancies. Of particular interest, in a previous study using a murine metastasis BCa model, Yang et al 8 observed that LISCH7 is one of the most upregulated metastasis-related genes.…”
Section: Introductionmentioning
confidence: 99%